Exploring Ecoacoustic Trajectories in a Giant Sequoia Forest After Wildfire - Meyer, Erik; Fristrup, Kurt; Caprio, Anthony C.; Seale, L. Don; Linares, Carlos; McKenna, Megan F. (Frontiers in Remote Sensing, 2022)
Forest management strategies that create spatially diverse fire-caused disturbance outcomes, consistent with historic fire regimes, are a desired condition for fire adapted western United States forests. In this context, the temporal dynamics of forest response to fire can inform the tempo and scale of forest management, including prescribed burning. Here, we investigated the use of ecoacoustic methods to assess ecological condition in a four-year period (2016-2019) after wildfire in a giant sequoia forest landscape within Kings Canyon National Park, California, USA. Audio recorders at nine sites were deployed soon after the 2015 Rough Fire subsided. The monitoring sites were located in regions with different fire histories, representing five fire history categories. We used the Acoustic Complexity Index (ACI) to document biotic chorus complexity. This previously tested ecoacoustic index provided a daily indicator of biotic sound activity in frequencies dominated by avian calls. Patterns in ACI were evaluated using generalized additive mixed models to understand the relationship with time-since-fire and covariates that accounted for season, fire history category, and weather conditions. We showed that time-since fire and fire-history influenced patterns in ACI after accounting for season and air temperature effects. Monitoring sites where prescribed fire preceded the Rough Fire showed the highest predicted ACI and evidence for a relatively consistent seasonal pattern in ecoacoustic activity across subsequent seasons. Sites without prescribed fire and burned by the Rough Fire exhibited the most pronounced successive decreases in ACI in the first and second years after the fire. The daily temporal resolution of the ecoacoustic index also revealed phenological shifts related to time-since-fire and fire history. Sites unburned by the Rough Fire offered some context for how fire changed ecoacoustic activity post-wildfire, however evidence suggested they were also impacted by the presence of the nearby Rough Fire. The patterns in the ecoacoustic index when combined with vegetation surveys offered complementary insights into ecological dynamics of regeneration after fire. Our exploratory analysis showed that using ecoacoustic methods in wildfire monitoring offers a scalable approach to remote sensing of ecological trends. Archived recordings from the monitoring effort afford future opportunities for new or more detailed insights.